Behavioral Problems With Management by Objectives - Jamieson, Bruce (Academy of Management Journal, 1973)
This paper is concerned with some of the often neglected behavioral problems associated with the practice of management by objectives. These include problems relating to managerial style, adapting to change, interpersonal skills, setting objectives, measurement, and management by objectives quality control. The paper concludes with some criticisms of the current state of management by objectives research.